A polymorphism in the FAM13A gene confers protection against tuberculosis in Brazilian workers exposed to silica - Marcos César Santos de Castro; Angela Santos Ferreira Nani; Kaio Cezar Rodrigues Salum; Lucas de Carvalho Costa; Valéria Barbosa Moreira; Hermano Albuquerque de Castro; Patrícia Canto Ribeiro; Walter Costa; Cícero Brasileiro de Mello; Fabiana Barzotto Kohlrausch (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis, which was recognized by the World Health Organization (WHO) as a global epidemic in 1993. TB is the leading infectious disease associated with silicosis, with studies showing an increased risk when compared to healthy individuals. We conducted an association study to evaluate the influence of polymorphisms in the ACE, FAM13A, FAS, FASLG, IL1RN, NOS2, TGFB1, and TNF genes on TB susceptibility. Methods: Nine polymorphisms were genotyped using Polymerase Chain Reaction (PCR) in a sample of 143 patients with silicosis in Rio de Janeiro (RJ), Brazil. Results: Seventy (49%) patients had a confirmed prior diagnosis of TB, of whom 25 (35.7%) had simple silicosis and 45 (64.3%) had complicated silicosis. The TG genotype of rs2609255 in FAM13A showed a protective effect against TB (OR=0.46; 95% CI: 0.22-0.98; p=0.040) compared to the GG genotype, and also when compared to the two combined homozygous genotypes (TT+GG) (OR=0.43; 95% CI: 0.20-0.90; p=0.024). Logistic regression analysis, including independent clinical variables, confirmed the protective effect of the TG genotype. Conclusion: This study suggests that the rs2609255 polymorphism in FAM13A may play a role in TB risk among patients with silicosis. Given the limited research on genetic polymorphisms and TB susceptibility in silicosis patients, further studies are needed to validate these findings.